RELASI MAKNA DALAM PUISI YANG SEDARI TADI DUDUK MEROKOK DI HADAPANMU KARYA HERWAN FR - Euis Khaeryana; Nazwa Dwi Amalia; Dodi Firmansyah (STKIP Subang, 2024)
This research analyzes the relationship between the meanings of synonyms and antonyms in a collection of poems entitled